Hydrochemical Study of the Southern Sector of the Al-Massab Al-Aam Canal Water, Southern Iraq - Asd, Waleed H.; Ghalib, Hussein B.; Alzubaydi, Jaffar H. (Iraqi Journal of Science, 2022)
Al- Masab AL-Aam canal (or the Main Drain) is a vital strategic project in Iraq. It collects the drain water from the agricultural lands and drains to the Arabian Gulf via Shatt Al-Basra. Fifteen water samples were collected from different sites along the course of the Al- Masab Al-Aam canal southern sector extending from Nasiriyah Basra to evaluate the hydrochemical properties. The variation of the sediment’s texture along the southern sector was investigated. The results reflected that the sediment is characterized by the presence of sand, silt, and clay. It is noted that the amount of salt in the water increases during the summer when temperatures are rising, and consequently, the evaporation rate increases. Changes in the saturation index also continuously affect the dissolution and precipitation of minerals along the river. The results of the saturation index analysis showed that the relationship between sulfate concentration and mineral saturation coefficients tends to increase their solubility for most minerals. The importance of the research lies in knowing and identifying the factors causing the change in water quality through studying the hydrological and hydrochemical properties of water and comparing the results to find out the reasons for the increase and decrease in its concentrations along the study area.